Revisiting enterprise politics in the interwar Hungary: The case of The Rimamurány–Salgótarján Iron Works Co: Worker‘s lifestyle and rate of living on the colony of the steel factory in Salgótarján before the World War II - Várkonyi-Nickel, Réka (METSZETEK Társadalomtudományi Folyóirat, 2018)
-